Impaired cognitive flexibility in schizophrenia: A systematic review of behavioral and neurobiological findings - Philipp Aumer; Geva A. Brandt; Dusan Hirjak; Florian Bähner (Biomarkers in Neuropsychiatry)
Background and hypothesis: Impaired cognitive flexibility in schizophrenia (SZ) is well documented and correlation with worse functional outcome indicates clinical relevance. Paradigms that assess cognitive flexibility include the Wisconsin Card Sorting Test (WCST) and the Cambridge Neuropsychological Test Automated Battery’s (CANTAB) Intra-Extra Dimensional Set Shift (IED). This systematic review provides an overview of the current state of research on cognitive flexibility in schizophrenia and points out relevant areas of non-consensus. Methods: Two electronic databases (Embase and PubMed) were searched for records published from 1993 to 2024 on adult SZ patients that were assessed for cognitive flexibility/set-shifting ability using WCST and/or IED. Results: 38 studies were included in the review, most of which reported significantly worse performance of SZ patients in WCST and/or IED compared to healthy controls (HC). Most publications focused on the specific profile of cognitive inflexibility. Other aspects included progression of cognitive inflexibility over the course of the illness, neurobiological correlates, IQ as a possible confounder and whether cognitive inflexibility is a heritable trait. Conclusion: Included studies show that cognitive inflexibility rather reflects a stable trait than a state, indicating a lasting prefrontal impairment in SZ. Further longitudinal studies are needed to clarify how these deficits evolve during progression of the disorder. Neither antipsychotic medication nor intelligence seem to explain impaired cognitive flexibility. However, a disease-specific cognitive phenotype has not yet been established and additional research on neuro-computational mechanisms is thus needed to identify possible targets for interventional studies.